138: Prescribing Long-Term Asthma Controller in Poorly Controlled Children with Persistent Asthma: Reported Behaviour, Facilitators and Solutions. Issue 5 (1st June 2015) - Ducharme, F; Lamontagne, AJ; Pelaez, S; Grad, R; Lavoie, K; Ernst, P; McKinney, ML; Bacon, S; Guay, H; Collin, J; Blais, L
Abstract: BACKGROUND: Despite clear guidelines, many school-aged children with persistent asthma are not prescribed long-term asthma controller by their physician. OBJECTIVES: To identify of key facilitators and solutions proposed by physicians to facilitate long-term prescription of asthma controller in children with persistent asthma (for ≥3 months or until follow-up with the treating physician). DESIGN/METHODS: We designed a two-phase mixed methods study. Following a qualitative study in which physicians proposed numerous facilitators and solutions to increase the prescription of long-term asthma controller, we developed a quantitative 175 item-questionnaire seeking physicians' endorsement of proposed solutions and likely behaviour in one of four case vignettes of an individual (school-aged child or adult) with poor asthma control seen in the acute care or clinic setting. Using the Tailored design method, the questionnaire was sent to randomly-selected paediatricians (n=209), general practitioners (GP, n=525) and emergency physicians (EP, n=103), representing respectively 29%, 6% and 73% of the physician census tract of the College des médecins du Québec. Results are presented as weighted proportions. We focus this report on responses to the pediatric cases. RESULTS: After excluding 89 non-eligible physicians, we obtained a 56% participation rate (n=421) with 212 (115 paediatricians, 79 GP, and 18 EP) selecting a paediatric vignette (58% acute care; 42% clinic setting). Participants were predominantly women (79%), paediatricians (54.2%), practicing for a median of 11.5 years in an academic (53%) environment. Most physicians correctly identified the child as having uncontrolled (72%), persistent (81%) asthma and would have prescribed a long-term asthma controller (83%). The following resources greatly increased physicians' comfort in prescribing a long-term asthma controller: patient asthma education, use of lung function testing, concurring opinion from and access to specialists, frequent medical follow-ups, and the implication of allied healthcare professionals in patient self-management. Physicians highly endorsed proposals for: inter-professional team approach to patient self-management, professional education on asthma management, memory aids, computerized decision support tools, and computerized systems of waiting time for various health referrals. CONCLUSION: A large majority of surveyed physicians reported prescribing long-term asthma controller to the uncontrolled patient in the selected vignette, attesting to their general intention. An inter-professional team approach to guide patient self-management with allied health professionals, physician educational sessions, patient asthma education, decision support tool, and computerized waiting time for referrals were highly favoured by physicians treating children with asthma.